A Literature Review on Persuasive Communication: Utilising Elaboration Likelihood Model to Understand Consumer Engagement on Social Media Platforms - Mardhatilah, Dina; Omar, Azizah; Septiari, Elisabet Dita (Journal of Technology Management and Business, 2023)
The public’s consumption of social media has experienced a significant increase. This trend encourages marketers to use social media platforms to market their business and boost consumer engagement. Though studies have been conducted on the public’s consumption of social media and several theories anticipating consumer behaviour, motivation, and technological adoption have been developed, research into the relationship between marketing and promotional communications and consumers’ attitudes and choices has been limited. For example, the Elaboration Likelihood Model (ELM), which is a reasonable and viable model capable of explaining disposition and conduct in influential marketing communication, has remained unnoticed by researchers. The purpose of this study was to ascertain whether persuasive messages used in social media marketing could effectively increase consumer engagement (CE) using ELM. This research employed the search terms ‘elaboration likelihood model, consumer engagement, and social media’ on a Scopus-indexed academic database, dated from 2018 to 2023. A total of 16 articles were selected following a screening stage. The administered systematic literature review suggests that ELM provides a hypothetical direction to arranging online entertainment content angles (i.e., focal and fringe signs) and recognising the variables that influence consumer engagement. A greater understanding of how to build consumer engagement on social media platforms through ELM can give insight into developing effective strategies for marketers. Future research can use the current study to improve research on social media and consumer engagement by using and expanding ELM.